A job trial subsidy for youth: Cheap labour or a screening device? - Márton Csillag; Balázs Munkácsy; Judit Krekó; Ágota Scharle (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
This paper evaluates a 90-day hiring subsidy designed for young jobseekers aged below 25, introduced in Hungary in 2015 as part of the Youth Guarantee programme. The subsidy covers the total wage cost with no obligation to retain the new hire when the subsidy expires. The analysis is based on linked administrative data taken from the unemployment register, cognitive skills measured at age 15, health and social security records. The causal impact of the subsidy on subsequent employment is identified in comparison to participants of a largescale public works programme, using propensity score matching with exceptionally rich controls. The estimates indicate significant positive effects: participants spent 14-20 days more in employment within six months after the programme ended on the whole sample. The impact is weaker on the 12-month horizon. We find that the subsidy works well as a screening device: the programme has the highest impact on those workers who have very low levels of schooling (eight years of primary school or less), but demonstrated high skill levels on standardised competence tests. One potential explanation is that employers tend to retain those with better cognitive skills, irrespective of their formal qualifications. We also find some indication that the subsidy is (mis)used by some employers to hire short term, seasonal workers.
Keywords: J08; J64; J68; 330; youth unemployment; ALMP; Youth Guarantee; wage subsidy; public works; propensity score matching